FAKTOR RISIKO KESEGARAN JASMANI SISWI SMA MUHAMMADIYAH 1 PONOROGO Risk Factors of Physical Fitness among Female Student in Muhammadiyah 1 Ponorogo High School - Ikanov Safitri; R. Bambang Wirjatmadi (Universitas Airlangga, 2020)
Physical fi tness is the ability of each individual to carry out various daily activities without feeling fatigue. Physical fi tness is useful as a supporting capacity for the physical activity of children therefore it is expected to improve their health and achievement. Factors that infl uence physical fi tness include genetics, age, gender, physical activity, nutritional status, food intake, haemoglobin level, resting time and smoking habits. The purpose of this study was to analyze the risk factors of physical fi tness among female students in Muhammadiyah 1 Ponorogo High School. This case control study included 50 female students and divided into 25 cases and 25 controls. Chi-Square test was used to analyze the relationships between variables. The results showed that there was an association between protein adequacy (p=0.023) OR = 11.3 and haemoglobin levels (p=0.049) OR = 9.3 with physical fi tness. While the adequacy of iron (p=0.345) did not associated with physical fi tness. Student with low protein adequacy and haemoglobin level have respectively 11.3 and 9.3 times higher risk of having low physical fi tness than student with good protein adequacy and haemoglobin level.